Minimum Reporting Standards for in vivo Magnetic Resonance Spectroscopy (MRSinMRS): Experts' consensus recommendations. (9th February 2021) - Lin, Alexander; Andronesi, Ovidiu; Bogner, Wolfgang; Choi, In‐Young; Coello, Eduardo; Cudalbu, Cristina; Juchem, Christoph; Kemp, Graham J.; Kreis, Roland; Krššák, Martin; Lee, Phil; Maudsley, Andrew A.; et al.
Abstract : The translation of MRS to clinical practice has been impeded by the lack of technical standardization. There are multiple methods of acquisition, post‐processing, and analysis whose details greatly impact the interpretation of the results. These details are often not fully reported, making it difficult to assess MRS studies on a standardized basis. This hampers the reviewing of manuscripts, limits the reproducibility of study results, and complicates meta‐analysis of the literature. In this paper a consensus group of MRS experts provides minimum guidelines for the reporting of MRS methods and results, including the standardized description of MRS hardware, data acquisition, analysis, and quality assessment. This consensus statement describes each of these requirements in detail and includes a checklist to assist authors and journal reviewers and to provide a practical way for journal editors to ensure that MRS studies are reported in full. Abstract : This paper sets out the expert consensus on minimum reporting guidelines for MRS studies. It includes a checklist as a practical way for authors and journal editors to ensure that MRS studies are reported appropriately. A common set of reporting standards will greatly increase transparency, rigor, and replicability of MRS studies, and should further the successful integration of MRS into widespread clinical practice.